2018
DOI: 10.3906/kim-1612-65
|View full text |Cite
|
Sign up to set email alerts
|

Protein ion-exchange chromatography on a biomacromolecule-immobilized monolithic cryogel

Abstract: An efficient and inexpensive monolithic stationary phase (PHEMA-HA) has been prepared through an easy process comprising addition of humic acid (HA) to a mixture of 2-hydroxyethyl methacrylate (HEMA) and N,N'methylenebisacrylamide (MBAAm) and subsequent radical-polymerization at -20 • C. The prepared monolithic material was characterized in terms of various techniques and methods such as elemental analysis, FTIR spectroscopy, scanning electron microscopy, mercury porosimetry, hydrolytic stability tests, pH pzc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Results showed that more than 80% of PHEMA-PDA structure was fully occupied by water molecules. This is a very typical behavior observed for cryogels (Özkan et al, 2018;Perçin et al, 2015) and confirms macroporous morphology and hydrophilic nature of PHEMA-PDA. Thus, PDA-coating process was found not to have a negative impact on the porous structure of the studied cryogel matrix.…”
Section: Fig 3 Determination Of Phpzc By the Mass-titration Methodssupporting
confidence: 78%
“…Results showed that more than 80% of PHEMA-PDA structure was fully occupied by water molecules. This is a very typical behavior observed for cryogels (Özkan et al, 2018;Perçin et al, 2015) and confirms macroporous morphology and hydrophilic nature of PHEMA-PDA. Thus, PDA-coating process was found not to have a negative impact on the porous structure of the studied cryogel matrix.…”
Section: Fig 3 Determination Of Phpzc By the Mass-titration Methodssupporting
confidence: 78%